Estimation of macrodispersion in 2‐D highly heterogeneous porous media using the Eulerian‐Lagrangian localized adjoint method. Issue 1 (10th January 2013) - Ramasomanana, Fanilo; Younes, Anis; Ackerer, Philippe
Key Points Validation of first and higher order stochastic theories Effects of local dispersion on macrodispersion Required travel distance to reach Fickian regime